Crystallization of NaHCO 3 for concomitant CO 2 sequestration and enrichment of lithium cations concentration in high salinity brines - Vera, Maria Laura (2025)
Continental brines, with total dissolved solids ranging from 170-350 g L-1, are the mostabundant lithium resources, although lithium is one of the minor brine components, atconcentrations around 1%. Amongst several requirements, for an efficient lithium recovery, it isimperative to improve the Li+ to Na+ concentration ratio. Here we report a membrane electrolysis process for Na+ abatement from brines avoiding solid incrustations inside the reactor and minimizing lithium losses. Sodium is precipitated by CO2 absorption and conversion tobicarbonate anions under basic conditions. Variables such as CO2 flow rate and applied currentdensities were modified under different experimental designs. Three different arrangementswere tested, with the best results found for an uncoupled CO2 conversion and the recovery ofthe effluent from solid washing. Following this strategy, a reduction in the Na+ content of approximately 70% was achieved with a decrease of more than 3-fold in the Na+/Li+ ratio of concentrations. Lithium recoveries of up to 66.6% in the catholyte were obtained with a mass balance close to 100% for both lithium and sodium. The proposed methodology has thepotential to capture about 146.4 g of CO2 per liter of electrolyzed brine, permanently storing CO2as mineral carbonates.